Pengaruh Reward dan Punishment Guru terhadap Resiliensi Anak Usia Dini Kelompok B di Taman Kanak-kanak Negeri Pembina Kabanjahe - Saragih, Agustina Phipeliny; Menanti, Asih; Surbakti, Amanah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the effect of giving rewards and punishments to the resilience of the children of the TK Negeri Pembina Kabanjahe TA. 2020/2021. The research method is a quantitative descriptive correlational type by placing the research variables in two groups, namely the independent variable and the dependent variable. The research population is the children of the Kabanjahe State Kindergarten. The sampling technique used was the Saturated Sampling technique with a selected sample size of 30 children, the data collection method used an observation sheet for giving rewards, giving punishment, and child resilience. Analysis of research data shows that (1) there is a significant effect between reward giving and children's resilience as indicated by the coefficient R = 0.521 and p = 0.000, namely p < 0.05; (2) there is a significant effect of giving punishment to children's resilience, which is indicated by the coefficient R = 0.655 and p = 0.008, namely p <0.05 and (3) there is a significant effect of giving rewards and giving punishment to children's resilience which is indicated by the coefficient F = 21.596 and R (regression coefficient) = 0.657 while R2 = 0.431 with p < 0.05 and Std. Error of the Estimate 6,1055, The accuracy rate is 100% - 6,1055= 93,8945%. The analysis used is Multiple Regression Analysis and Wilcoxon.parental support; self-concept; and self-confidence of students.